2010
DOI: 10.1097/jto.0b013e3181c07c6c
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Amrubicin for Second-Line Treatment of Advanced Non-small Cell Lung Cancer: Results of the West Japan Thoracic Oncology Group Trial (WJTOG0401)

Abstract: Amrubicin is a possible alternative for second-line treatment of advanced NSCLC, although a relevant hematological toxicity is significant, especially with a febrile neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…A more recent phase II study in Japan found that amrubicin monotherapy was efficacious and safe as a second-line treatment for advanced NSCLC previously treated with platinum-based chemotherapy, and the results showed a response rate of 11.5%, an OS of 8.5 months and a 1-year survival rate of 32%, all of which were comparable to the results obtained with other second-line treatment regimens, including docetaxel, pemetrexed and erlotinib [16]. A study of the efficacy of chemotherapy as a salvage regimen in heavily pretreated NSCLC patients reported that the response rates of 43 patients (extracted from over 700 patient records with recurrent NSCLC) who had received two prior chemotherapy regimens including platinum and docetaxel for recurrent NSCLC decreased with each subsequent line of treatment (third-line 2.3% and fourth-line 0%), that the disease control rate also decreased (third-line 30.2% and and fourth-line 21.4%), and that the overall MST from the start of the final line of treatment was 4 months [20].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A more recent phase II study in Japan found that amrubicin monotherapy was efficacious and safe as a second-line treatment for advanced NSCLC previously treated with platinum-based chemotherapy, and the results showed a response rate of 11.5%, an OS of 8.5 months and a 1-year survival rate of 32%, all of which were comparable to the results obtained with other second-line treatment regimens, including docetaxel, pemetrexed and erlotinib [16]. A study of the efficacy of chemotherapy as a salvage regimen in heavily pretreated NSCLC patients reported that the response rates of 43 patients (extracted from over 700 patient records with recurrent NSCLC) who had received two prior chemotherapy regimens including platinum and docetaxel for recurrent NSCLC decreased with each subsequent line of treatment (third-line 2.3% and fourth-line 0%), that the disease control rate also decreased (third-line 30.2% and and fourth-line 21.4%), and that the overall MST from the start of the final line of treatment was 4 months [20].…”
Section: Discussionsupporting
confidence: 69%
“…The question of whether an interaction exists between the histological subtype of NSCLC and amrubicin efficacy has been a matter of controversy, because 1 phase II study demonstrated a higher response rate to amrubicin monotherapy in a group of patients with adenocarcinoma (36.4%) than in a group with squamous cell carcinoma (11.5%) [14], while another phase II study reported finding no clear correlation between tumor histology and response to amrubicin monotherapy [16], and there have been no preclinical reports that investigated whether there is a correlation between amurubicin efficacy and the histological subtypes of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we decided to investigate the predictive factors associated with grade 3–4 (<1,000 and ≥500/mm 3 ) rather than grade 4 (<500/mm 3 ) neutropenia in the present study. In this study, the incidence of grade 3–4 neutropenia was 62% (38/61), which was a little lower than that in previous phase II studies (median 78%; range 39–97%) [4,5,6,7,8,9,10,11,12,13,14]. Multivariate logistic analysis revealed that higher doses of AMR, female gender, and lower baseline hematocrit values were significant predictors of grade 3–4 neutropenia in patients with lung cancer treated with AMR monotherapy.…”
Section: Discussionmentioning
confidence: 45%
“…In phase II trials of second- or third-line AMR monotherapy for the treatment of SCLC, the response rates and the overall survival were 21–53% and 6–12 months, respectively [4,5,6,7,8,9,10,11]. In the treatment of NSCLC, the response rates of AMR monotherapy were 12–28% [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%